Determinants of inequalities in welfare among households in Ethiopia: A comparative study of urban and rural Ethiopia - Tsegamariam Dula Sherka; Jemil Yasin; Haymanot Meseret; Abrham Seyoum (Cogent Economics & Finance, 2023)
This study aims to investigate welfare inequality between households in rural and urban Ethiopia using secondary data obtained from the Living Standards Measurement Surveys (LSMS) available on the World Bank website. The data was analyzed using the Atkinson Index to identify welfare inequality among households and quantile regression to identify determinants of welfare inequality in rural and urban Ethiopia. The results show that the Atkinson index for the rural group is 0.123006, while it is 0.110899 for the urban group, indicating a higher level of welfare inequality in rural areas. Furthermore, the quantile regression analysis reveals that among the factors measured, the number of assets, access to health services, and saving are important determinants of welfare inequality in rural households. On the other hand, the number of livestock and household size are found to be significant factors contributing to welfare inequality in urban areas. This study provides valuable insights into the specific drivers of welfare inequality in both rural and urban settings and can inform policymakers on how to address these inequalities to promote social and economic development in Ethiopia.
Keywords: 330; Atkinson Index; Ethiopia; inequality; Lorentz curve; quantile regression; rural and urban; social and economic development; welfare